'No one is larger than the state.' Consent, dissent, and vigilant violence during Turkey's neoliberal urban transition. Issue 2 (3rd April 2021) - Polat, Defne Kadıoğlu
ABSTRACT: Tophane is a conservative quarter in central Istanbul that has become known for its political support of the ruling Justice and Development Party (AKP). This support has included violent vigilantism against oppositional groups. In the last decade, since gentrification has become more tangible in the area, violence has also turned against perceived newcomers and outsiders. Gentrification, however, is openly condoned and politically enforced by the AKP. Taking the neoliberal transformation of a neighbourhood in Istanbul that displays strong support for the governing party, as a starting point, this article engages with the governance of dissent and the production of consent on the sub-city level. I employ the Gramscian notion of the integral state to argue for a dialectical understanding of consent production in which consent and coercion are seen as intertwined, rather than opposed. To specify this point, I focus on the important, yet ambiguous, role of local state- and party-cadres (local intermediaries) in Istanbul's urban governance. Drawing on ethnographic fieldwork and interviews, I show that the neighbourhood in Turkey is a crucial political arena in which intermediaries function as important links between civil society and the state apparatus.